2021
DOI: 10.20473/mkp.v34i32021.305-316
|View full text |Cite
|
Sign up to set email alerts
|

Power relation of the 212 Islamic Group and the government in the 2019 presidential election

Abstract: The 212 Islamic Group was in opposition with the government of Joko Widodo (Jokowi) in the 2019 presidential election. This group made militant resistance against Jokowi in the presidential election. This resistance influenced the presidential election contestation became more dynamic and fierce. The fierce contestation had divided the community into two camps, namely the pros and cons of Jokowi. This study explored and analyzed the resistance of the 212 Islamic Group against the government in the 2019 preside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Despite a relatively enthusiastic local government response to the digital transformation initiative, scholars and previous research have indicated a weakness in the implementation of SPBE (Asianto and Firmansyah, 2022;Astuti et al, 2021;Muzaqqi and Fitrianto, 2023). Our fieldwork further unveiled that there were cases where local governments had struggled to provide proper e-government systems and were therefore not too optimistic about achieving SBPE targets.…”
Section: The Electronic Government Systemmentioning
confidence: 63%
See 2 more Smart Citations
“…Despite a relatively enthusiastic local government response to the digital transformation initiative, scholars and previous research have indicated a weakness in the implementation of SPBE (Asianto and Firmansyah, 2022;Astuti et al, 2021;Muzaqqi and Fitrianto, 2023). Our fieldwork further unveiled that there were cases where local governments had struggled to provide proper e-government systems and were therefore not too optimistic about achieving SBPE targets.…”
Section: The Electronic Government Systemmentioning
confidence: 63%
“…It was one of the most ambitious decentralisation endeavours, involving the implementation of political, administrative, and fiscal decentralisation within a context characterised by a diverse range of regional socio-economic attributes, cultural and ethnic diversity, and notably, limited prior experience with decentralisation (Brodjonegoro, 2003; Diprose et al, 2019). The powers transferred encompassed a wide spectrum of responsibilities, spanning health, primary and secondary education, public works, environmental management, communication, transportation, agriculture, manufacturing, and various other economic sectors (Nasution, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Setelah penetapan Ahok sebagai tersangka, tidak menjadikan kelompok Islamisme ('Kelompok Islam 212'), mengurangi aksi-aksi agama dan politik (M. M. Muharam et al, 2021). 'Kelompok Islam 212' secara aktif melakukan gerakan politik agar Ahok tidak terpilih kembali sebagai Gubernur DKI Jakarta pada pemilihan gubernur (pilgub pada 2017).…”
unclassified